Ergonomic risk assessment with rula and ocra method in a garment workshop. Case study - Espichan Araujo, Khryst (2025)
This research focused on micro and small enterprises (MSEs) which comprise 96% of the textile industry in Peru. This sector is the most important manufacturing activity. Work-related musculoskeletal disorders (MSD) were identified with methods such as RULA and OCRA, which evaluates upper extremities. The purpose of this research is to reduce MSDs generated by activities performed in garment workshops by making use of ergonomic methods for the detection of inadequate postures and subsequently propose an improvement by applying engineering methodologies such as workstation redesign and ergonomics. After implementing the improvements, all the garment makers improved their score in the RULA method, reducing the risk by up to 42.9%. On the other hand, the OCRA method reduced the exposure index from a very high risk to a medium risk.